Big Data at the service of teaching and scientific research within the UAE - ABDELOUARIT, Karim AOULAD; ., Noura AKNIN (Journal of Education and Vocational Research, 2015)
With the emergence of the digital world, data access has become an action as quick and direct that many questions arise about the reliability and value of information. However, the data returned by the online search engines are based on an open and massive environment, which include data of any type, which come from different sources of information. Indeed, in the field of education and especially when using online search, the learner is left with a set of heterogeneous information that does not exist in an orderly format and are not easy to consume. This aspect of data variety represents the second V in the design of the Big Data phenomenon. With the aim to support learners in their search for information, it is proposed to design a specialized structuring tool to combine process and classify the variety of these massive data so they can provide the best result to the learner. The present article deals with the descriptive study of the current state of using online search by UAE’s students, and the proposal to explore new methods and approaches through experimentation of our solution for open and massive data environment, in order to enhance learning and scientific research in the UAE.